(untitled) (Revista Contexto & Educação, 2023)
This study aimed to analyze how critical and collaborative actions can contribute to the formation of conscious and reflective teachers about existing environmental problems, and the importance of critical environmental education in the discussions of science education. Therefore, in a qualitative approach, the investigation took place in the Science Teaching discipline of the Pedagogy course at the Federal University of Paraíba, in a critical-collaborative way. As a result, we could observe that science teaching, due to its proximity to the themes of environmental issues, should emphasize the complex historical and social apparatus of the theme in the classroom, favoring investigative activities, also stimulating the students’ criticality about the quoted theme.